Nanoemulsions Properties, Fabrications and Applications - Seng Koh, Kai; Loong Wong, Voon (IntechOpen, 2019)
Fluidics, an increasingly examined topic in nanoscience and nanotechnology is often discussed with regard to the handling of fluid flow, material processing, and material synthesis in innovative devices ranging from the macroscale to the nanoscale. Nanoemulsions - Properties, Fabrications and Applications reviews key concepts in nanoscale fluid mechanics, its corresponding properties, as well as the latest trends in nanofluidics applications. With attention to the fundamentals as well as advanced applications of fluidics, this book imparts a solid knowledge base and develops skill for future problem-solving and system analysis. This is a vital resource for upper-level engineering students who want to expand their potential career opportunities and familiarize themselves with an increasingly important field.